Development of Iot-Based Wind Speed, Temperature, and Humidity Monitoring - Arincia, Meicella Rizky; Hamdani, Dedy; Purwanto, Andik (Universitas Syiah Kuala, 2024)
This study aims to overcome the lack of weather monitoring tools in Indonesia. The main factors of extreme weather changes in Indonesia are the rainy season and strong atmospheric dynamics. Weather monitoring tools developed based on IoT, allowing monitoring remotely. The research method used the ADDIE model, with data collected through validation tools and analyzed qualitatively using the Likert scale. Validation by three experts showed an average result of 89.29%, which falls into the very decent category. This tool aims to provide solutions for coastal communities in the city of Bengkulu, allowing them to get early warnings about weather changes, especially strong winds. This tool has been proven to fit its design and works well. Recommendations for future research are the addition of regional classification, replacement of more durable sensors such as other types of DHT sensors, and the addition of data loggers to store previous measurement history.